Komunikasi Interpersonal Orang Tua Tunggal dalam Menjalin Hubungan Emosional dengan Anak - Nasir, Nasir (Jurnalika : Jurnal Ilmu Komunikasi, 2025)
This study aims to examine the form and quality of interpersonal communication carried out by single parents in establishing emotional relationships with children. The background of this research is based on the fact that single parents face psychological, social, and economic challenges that can affect communication patterns with children. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The subjects of the study were several single parents who had school-age children and were domiciled in a particular region. The results of the study show that interpersonal communication carried out by single parents is generally open and empathetic, both verbally and nonverbally. Warm and consistent communication patterns play a big role in building emotional attachment and a sense of security in children. However, time constraints, work pressure, and psychological conditions are the main obstacles in maintaining the quality of communication. Nonetheless, single parents who are able to create meaningful communication routines, such as eating together or bedtime conversations, can still build a strong emotional connection with their child. This research contributes to the development of family communication science, especially in the context of non-conventional families, as well as provides practical insights for single parents in building effective communication and supporting children's emotional development.